Penggunaan Permen Sebagai Alat Tukar Pengganti Uang - Kilian, Siti Ramla; Tjoanda, Merry; Narwadan, Theresia Nolda Agnes (TATOHI: Jurnal Ilmu Hukum, 2024)
Introduction: The use of candy as a medium of exchange for money is an act of diverting money in the form of candy by business actors to consumers. This is because business actors do not have coins to return to consumers, so candy will be used as a means of change.Purposes of the Research: The purpose of this research is to discuss whether candy can be used as a medium of exchange for money.Methods of the Research: By using the research method of normative juridical law (legal research). Type of descriptive analysis research. Sources of legal material consist of: a) primary legal material, namely law number 7 of 2011 concerning currency, law number 23 of 1999. b) secondary legal material, namely: doctrine, legal literature theories, research results and articles scientific. Tertiary legal materials, namely legal dictionaries, Indonesian language dictionaries, and websites. Collection and analysis of legal materials, namely collecting data, compiling it methodically and then analyzing it qualitatively to get clarity about the problems being faced.Results of the Research: The results of this study are in article 2 paragraph 2 of Law Number 23 of 1999 concerning Bank Indonesia which states that: rupiah money is a legal tender in the territory of the Republic of Indonesia, then article 2 paragraph 3 which states that: every act that uses money or has the purpose of payment or obligations that must be fulfilled with money if done within the territory of the Republic of Indonesia must use rupiah currency, unless otherwise stipulated by Bank Indonesia Regulations, meaning that only money can be used as means of payment and with return, then business actors are obliged to use cash in every payment transaction.